Perencanaan Program Rumah Singgah Dompet Dhuafa Singgalang - Ahmad Faisal Hasibuan (IAIN Batusangkar, 2022)
The Shelter House is a temporary lodging place for non-formal patients, where the patient stays for a while before the completion of the outpatient care carried out by the patient. The purpose of this study was to determine the planning of zakat, alms, and waqf funds for the shelter program of the Amil Zakat Institute Dompet Dhuafa Singgalang, Padang city. The main problem in this study is the procedure for planning the shelter program for the Amil Zakat Institute Dompet Dhuafa Singgalang, Padang city. The type of research that the author uses is (field research) field research with qualitative descriptive methods. The data collection techniques that the author uses are field observations, interviews with the Amil Zakat Institute Dompet Dhuafa Singgalang and documentation. Data analysis techniques are data reduction, data presentation and conclusion drawing.The results of this study indicate that planning is to prepare steps for planning the distribution of ZISWAF, socializing, allocating ZISWAF funds, as well as planning mustahik criteria and administrative requirements for mustahik